2016
DOI: 10.1007/s00404-016-4160-4
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section and its impact on fertility and time to a subsequent pregnancy in Germany: a database analysis in gynecological practices

Abstract: CS is associated with an increased risk of sterility and a decreased number of subsequent pregnancies in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…4 However, the effects of a clinical history of CS on fertility and pregnancy outcomes are still under investigation, as reported by studies from Europe and the USA. [5][6][7] Conversely, other experts argued that the clinical and social circumstances that increased CS rates had an impact on reproductive health broader than the CS itself, reducing the effects of CS on future fertility to marginal. 8 The underlying causes of the lower fertility and adverse pregnancy outcomes after a previous CS are still unclear, but they may relate to implantation issues, with increased risk for early pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, the effects of a clinical history of CS on fertility and pregnancy outcomes are still under investigation, as reported by studies from Europe and the USA. [5][6][7] Conversely, other experts argued that the clinical and social circumstances that increased CS rates had an impact on reproductive health broader than the CS itself, reducing the effects of CS on future fertility to marginal. 8 The underlying causes of the lower fertility and adverse pregnancy outcomes after a previous CS are still unclear, but they may relate to implantation issues, with increased risk for early pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…and injury to the fetus are more likely in C-section (8)(9)(10). Also, several studies have reported that C-section is associated with reduced fertility (11). Due to these complications, WHO emphasized that only 10% -15% of deliveries should be undertaken through C-section (12).…”
Section: Introductionmentioning
confidence: 99%
“…Another study performed by Jacob L et al on 6483 patients in CS group and 6483 in VD group demonstrated that CS is associated with an increased risk of sterility and subsequent infertility in Germany. In this study, they found that CS decreased subsequent pregnancies as polycystic ovary syndrome and deterioration of menstrual cycle did it (16). Gurol-Urganci I et al assessing 1,047,644 first births to low-risk women using routinely collected data found that there is no or only a slight effect for CS on future fertility; they demonstrated that it is due to residual bias in their adjusted results that would lead to an overestimate of the effect of CS on fertility (17).…”
Section: Discussionmentioning
confidence: 57%